MRI scan with the “feed and wrap” technique and with an optimized anesthesia protocol: a retrospective analysis of a single-center experience - Moltoni, Giulia; Lucignani, Giulia; Sgrò, Stefania; Guarnera, Alessia; Rossi Espagnet, Maria Camilla; Dellepiane, Francesco; Carducci, Chiara; Liberi, Stefano; Iacoella, Elisabetta; Evangelisti, Giuliana; Contini, Anna; Campi, Francesca; et al. (Frontiers in Pediatrics, 2024)
Introduction MRI examinations in the pediatric population require acquiring motionless images in the safest possible manner. At our institute, we have developed a protocol called “Good Practice” aimed at avoiding anesthesia in newborns and infants through the use of the “feed and wrap” technique, as well as preventing hospitalization for older children requiring anesthesia with an optimized sedation protocol. We evaluated this protocol in terms of patient safety, imaging quality, and parental satisfaction. Materials and methods Patient data were collected retrospectively. In the feed and wrap group, image quality and the necessity of repeating the examination were evaluated. In the optimized anesthesiologic protocol group, various parameters were analyzed to assess the safety of the protocol. Parental satisfaction was determined through a questionnaire. Results A total of 132 patients were included, with 82 undergoing the feed and wrap technique and 50 receiving the optimized anesthesiologic protocol. In the feed and wrap group, images were classified as follows: 4.87% poor, 18.29% sufficient, 37.80% good, and 39.92% excellent. In only 2 cases a new MRI examination was required. In the optimized anesthesiologic protocol group, no adverse effects were observed, and no post-anesthesia hospitalizations were needed. 100% of parents of babies examined with the feed and wrap technique rated it as excellent. Furthermore, 85.6% of parents considered the optimized anesthesiologic protocol excellent, and 13.6% rated it as good. Conclusion At our institute, the feed and wrap technique proved to be effective in obtaining high-quality images. Anesthesia using propofol showed no adverse effects and proved to be successful in avoiding hospitalization. Parents expressed relief at the avoidance of anesthesia and hospitalization for their children.